Mora-dores numa roupa que pode se rasgar: vozes do povo camponês acerca do habitar na transposição do rio São Francisco. - Silva, Gabriel da (2023)
This investigation focuses on the Brazilian Northeast, a complex context historically associated with an arid climate and severe droughts. This scenario was, and still is, the stage for several governmental interventions that seek to promote improvements in an area understood as a problem situation. In this regard, more than a decade ago, the transposition of the São Francisco river reached the Northeastern "Sertão" with the promise of mitigating drought aggravations and promoting development for at least 12 million people. Due to the magnitude and the way in which it is being integrated, the transposition has some consequences in the territories and in the lives of peasants affected by the constructions. In this dissertation, the main objective was to understand the experience of relocation in the Vila Produtiva Rural (VPR) Salão, in Sertânia/PE, of the peasants who were expropriated by the constructions of the transposition of the São Francisco river. As specific objectives, we sought to discuss the conditions of expropriation and relocation of peasants in the context of the transposition of the São Francisco River; to present indicators that characterize the situation of the Covid -19 pandemic in the Northeast; to map the experience of peasants dispossessed by the transposition of the São Francisco River and relocated in Vila Produtiva Rural Salão, in Sertânia/PE, in the face of the Covid-19 pandemic; and point out ways that can guide the intervention of psychologists in the observed context. This experience has as a background the Covid-19 pandemic, which, when configured as a crisis in the ethical, political, economic, cultural, social and healthcare plans, had repercussions on the living experience of these groups. The methodological path consisted of a cartographic investigation, in dialogue with Gadamer's hermeneutic phenomenology. The intervention/research modalities, to collect the narratives, were the Logbook constructed by the researcher and the Conversation Circle carried out with four peasants who live in Vila Produtiva Rural Salão, in Sertânia/PE. For the analysis, an intersection of the research testimonies with scholars is proposed, in order to reveal the plots that constitute the reality of the peasant men and women present in the research. This moment was organized into three constellations that were interpreted by Gadamer's Philosophical Hermeneutics. It was revealed in the narratives that the residents of VPR Salão deal with precarious housing conditions added to the violation of rights and the non-fulfillment of promises made to them, who were expropriated and relocated. In this circumstance, belonging to the place of residence is called into question, since the right to dwell is still conditioned by the policy of government representatives. Added to this, the Covid-19 pandemic shows itself as a crisis that exposes the vulnerabilities of this context, accentuating the difficulties of access to health. Finally, despite these conditions, the narratives point out to possibilities for us to think of ways to accompany residents in their ways of living in VPR Salão, as well as to claim and build decent housing conditions.